Seagrass meadows for fisheries in Indonesia: a preliminary study. Issue 1 (September 2020) - Ambo-Rappe, R
Abstract: Seagrass meadows are among the most productive ecosystems on earth and are of great importance to support an abundance and diverse fish assemblages that form the basis for artisanal fisheries, especially in the tropics. Fisheries are vital in maintaining food security, and therefore the ecosystems that support these fisheries are also essential. Seagrass ecosystems contribute to fishery productivity, and seagrass fisheries are especially common in the Indo-Pacific region, where seagrass beds and their associated fauna are heavily exploited. However, these fisheries remain largely undocumented. Within the Indo-Pacific region, Indonesia contributes significantly to seagrass biodiversity and global seagrass extent. Seagrass fisheries undoubtedly exist in Indonesia, but publications on this topic are rare. Therefore, there is a need to highlight the extent, importance, and status of fisheries exploitation in the seagrass meadows of Indonesia. The aims of this study were to determine the importance of seagrass meadows in supporting fisheries productivity and examining the variability of seagrass fisheries in Indonesia. A literature search of published data on fisheries activities in seagrass meadows in Indonesia was conducted from March-May 2020. Google Scholar database was searched using the most specific keywords in English and Indonesian, for example, "seagrass" AND "fisheries" AND "Indonesia", "seagrass fisheries" AND "Indonesia", "Perikanan Skala Kecil" DAN "Padang Lamun", in the title, abstract or keywords, in order to obtain information from the few papers on seagrass fisheries in Indonesia published in English (international journals) and Indonesian. Additional data on seagrass fisheries and the fishing methods/gears used were collected by interviewing people who live or work in areas with few or no published data to gain a broader picture of seagrass fisheries in Indonesia. It was found that seagrass fisheries occur in almost all nearshore seagrass areas in Indonesia, including around many small islands. Many fishing gears are used in these fisheries, the most common being gill nets, traps, and gleaning (directly picking up fauna from the seagrass beds using bare hands or very simple tools). Therefore, from a socioeconomic perspective, seagrass beds are extremely important for the livelihoods of coastal and island communities in Indonesia.